2018
DOI: 10.1021/acs.jmedchem.8b01609
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Quinoxaline-Based κ-Opioid Receptor Agonists for the Treatment of Neuroinflammation

Abstract: Neuroinflammatory disorders, such as multiple sclerosis or experimental autoimmune encephalomyelitis (EAE), an established mouse model mimicking part of the human pathology, are characterized by inflammatory infiltrates containing T helper 1 (TH1) and TH17 cells, which cause demyelination and neurodegeneration. Disease onset and perpetuation are mediated by peripherally generated autoreactive T cells infiltrating into the central nervous system, where they are restimulated by antigen-presenting cells. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 68 publications
(130 reference statements)
3
44
1
2
Order By: Relevance
“…[12] Very recently, we showed that KOR agonists 1b (R=H) and 2 exhibit potent anti-inflammatory and immunomodulatory activity in primary mouse and human immune cells. Moreover, both KOR agonists led to almost complete protection of mice from developing MS-like symptoms in the MOG induced EAE [13] (Figure 1).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…[12] Very recently, we showed that KOR agonists 1b (R=H) and 2 exhibit potent anti-inflammatory and immunomodulatory activity in primary mouse and human immune cells. Moreover, both KOR agonists led to almost complete protection of mice from developing MS-like symptoms in the MOG induced EAE [13] (Figure 1).…”
Section: Introductionmentioning
confidence: 93%
“…For the synthesis of hydroxy and fluoro substituted KOR agonists of type 3, the synthetic route previously reported by us to obtain cis,trans-configured perhydroquinoxalines was pursued. [13,33,34] At first, the cyclic sulfuric acid ester amide 10 was prepared in seven steps starting from tetrahydroquinoxaline 9. [13] Nucleophilic ring opening of 10 by (S)-3-hydroxypyrrolidine led to secondary amine 11, which was acylated with 2-(3,4-dichlorophenyl)acetyl chloride to afford the amide 12a.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations